Pendekatan Lean Six Sigma Dalam Penentuan Prioritas Perbaikan Layanan Bank Berdasarkan Persepsi, Harapan Dan Kepentingan Nasabah - Hesti Budiwati (Jurnal Manajemen, 2017)
This research have a purpose to determine ofimprovement priority of bankingservicesbase  on  perception,  expectation  and  interest  level  of  the  customer  using  lean  sigsigma  approach.    The  result  of  this  research  are  expected  to  give  the  contribute  for  thebank  manager.  This  research  will  determine  to  recovery  priority  of  service  quality  of  thebank  consisted  of  (1)  effectiveness  and  assurance,  (2)access,  (3)  price,  (4)  tangible,  (5)service portofolio and (6) reliability.This research using lean sig sigma approach, to doingthe  calculation  unwighted  gap  and  weighted  gap  above  the  response  of    respondent  baseon  perception,  exspectation  and  interest  level  of  the  customer  above  the  response  of  theresponden  base  on  perception,  exspectation  and  interest  level  of  the  customer  aboveservive quality of the bank. The population of this research is all active customera at PT.BPR Arta Centra Asia Lumajang,and sample of this research is taken as 120 customer asrespondent.  The  result  of  this  research  showing  at  3  (three)  main  priority  of  the  recoveryquality  service  of  the  bank  that  is  dimension  to  reliability  for  the  item  the  dont  have  amistake  in  providing  service,  the  dimension  of  the  effectiveness  is  no  delay  because  thebirocation and procedure and service quickly.The next future this research are exspectedto  give  the  contribution  to  development  of  the  study  management  science,  especially  for marketing management service, so it can be a reference for the similiarity of research andadvance research.